Legal protection for farmers as consumers of subsidized fertilizers in the Brebes district, Central Java province - Serentyas santika; M utama (Institute Of computer Science (IOCS), 2023)
The government in the framework of realizing National Food Sovereignty, fertilizer is very important in increasing productivity and production of agricultural products, fertilizer is very decisive in achieving national food production targets. It is so important that fertilizer must be available in accordance with the six principles of right type, right quality, right amount, right time. , the right place, and the right price. Various efforts have been made by the government in the context of providing subsidized fertilizers to achieve the 6 (six) right principles. The government seeks to provide production facilities in the form of fertilizer in sufficient quantities offset by affordable prices for farmers. This is the basis for the government to impose fertilizer subsidies for farmers. This fertilizer subsidy policy is a policy implemented by the government in order to be able to provide incentives for farmers to increase food production and productivity, as well as increase farmers' income. Apart from playing a role in increasing productivity, fertilizer also improves the quality of agricultural commodities, through the application of appropriate cultivation technology using recommended production facilities. The effectiveness of the use of fertilizers is directed at the application of balanced and organic fertilization in accordance with the recommended fertilization technology technical standards in each specific location area. This subsidized fertilizer policy aims to ease the burden on farmers in supplying and using fertilizer for their farming activities.